2021
DOI: 10.1086/717886
|View full text |Cite
|
Sign up to set email alerts
|

The Single Motherhood Penalty as a Gender Penalty: Comment on Brady, Finnigan, and Hübgen

Abstract: Recent analysis has suggested that poverty rates, and their variation across rich countries, is driven much less by the prevalence of certain risks than by the poverty penalty attached to the risks. Focusing on single motherhood as a poverty risk, it is claimed the penalty attached to it is specific to the United States. This claim, we show, relies on models that condition on the major mechanisms through which poverty risks are heightened: the risk of non-employment, and of having only a single earner, in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…Conditioning on the characteristics of single mothers who are household heads and the characteristics (including full and part-time employment) of fathers in couples (who are frequently defined as the household head; see Moullin and Harkness 2021) has a more substantial effect, leading to a fall in the estimated income gaps across the income distribution in all countries. However, there are notable differences in magnitude.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Conditioning on the characteristics of single mothers who are household heads and the characteristics (including full and part-time employment) of fathers in couples (who are frequently defined as the household head; see Moullin and Harkness 2021) has a more substantial effect, leading to a fall in the estimated income gaps across the income distribution in all countries. However, there are notable differences in magnitude.…”
Section: Resultsmentioning
confidence: 99%
“…Single parents are defined as unpartnered household heads with dependent children under 18. A limitation of this measure is that it excludes single mothers who are not household heads, such as those living with their own parents, who may be particularly economically vulnerable (Moullin and Harkness 2021). However, it is not possibly to identify single mothers who are not household heads in all countries studied.…”
Section: Methodsmentioning
confidence: 99%
“…How women fare in the labor mar ket upon moth er hood (which is related to their mar i tal sta tus) has an impor tant bear ing on their eco nomic well-being if they become sin gle moth ers. Studies have shown that men who become sin gle par ents do not face the same pov erty pen al ties as women (Nieuwenhuis and Maldando 2018) because they do not suf fer the same labor mar ket pen al ties to par ent hood (Moullin and Harkness 2021). Consequently, the absence of a male bread win ner remains a major cause of sin gle moth ers' low income (Sigle-Rushton and McLanahan 2002), with impor tant impli ca tions for wel fare pol icy.…”
Section: Discussionmentioning
confidence: 99%
“…Motherhood is asso ci ated with large employ ment and earn ings pen al ties (Harkness and Waldfogel 2003;Kleven, Landais, Posch et al 2019), affect ing the incomes of all fam i lies with chil dren (Sigle-Rushton and Waldfogel 2007). However, such pen al ties are likely to be par tic u larly dam ag ing for sin gle moth ers, for whom reduced earn ings are cou pled with the absence of a male bread win ning part ner and pov erty risk is high (Moullin and Harkness 2021). Single fathers, by con trast, are much less likely to be liv ing in pov erty because they do not face the same labor mar ket pen al ties to par enthood (Moullin and Harkness 2021;Nieuwenhuis and Maldando 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation